Variações espaço-temporais no crescimento de Dalbergia nigra (Vell.) Allemão ex Benth - Vanessa Pontara (2014)
Spatio-temporal variation in soil resource availability associated with topography and seasonality may drive patterns of tree growth and phenology, but these links are poorly characterized for most tropical tree species. We use dendroecological methods to test the hypothesis that variation in topographic position is related to radial growth and phenology for individuals of the endangered tropical tree Dalbergia nigra under uniform conditions of climate and irradiance, and to examine effects of seasonality on plant phenology and growth periodicity. Dendrometer-based measurements of stem diameter change over 26 months and local measurements of soil nutrient and water availability were compared for 24 individuals of D. nigra distributed equally between summit and valley positions within a topographically heterogeneous fragment of Atlantic rain forest in southeast Brazil. Soil water and nutrient availability, and cumulative radial growth, were greater for trees in valley than summit positions. Monthly diameter increment was seasonal and positively related to monthly rainfall. D. nigra was seasonal in all phenophases, regardless of topographic position, and there were no differences in the frequency, timing or intensity of phenophases among topographic positions. We conclude that low soil nutrient and/or moisture availability reduce radial growth of D. nigra individuals growing in summit positions, while trees growing in valleys exhibit faster annual growth, but that vegetative or reproductive phenology are unaffected by fine-scale variation in topography.